Comparison of vertical forces in normal greyhounds between force platform and pressure walkway measurement systems - Besancon, M. F.; Conzemius, M. G.; Derrick, T. R.; Ritter, M. J. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
Peak vertical impulse (PVF) and vetical impulse (VI) data were collected from the left forelimbs and ipsilateral hind limbs of eight healthy adult Greyhound dogs ranging in mass from 27.30 to 36.36 kg. Walking velocity and acceleration were restricted to ranges of 0.9 to 1.1 m/s and −9.1 to 0.1 m/s2, resepctively. Data from the first 20 valid trials were analyzed for each dog on both systems. Forces were normalized and expressed as a percent of the dog’s body weight. Velocity and acceleration values were not statistically different in either set of trials. Evaluation of intra-dog variability via t-test revealed a statistical difference in two of 16 limbs (1/8 forelimb, 1/8 hind limb). The results indicate that the Tekscan walkway system is a viable alternative to the AMT1 model OR6-5 force platform for the generation of vertical impulse data. Statistically significant differences in peak vertical force values were noted between the two systems and were likely related to calibration times, but their clinical relevance appears negligible.
Keywords: Forceplate; pressure walkway; gait analysis; Tekscan; normal greyhounds